Multimodal response and writing as poetry experience - Pet, Sue Ringler; Mcverry, J Gregory; Obyrne, W Ian (Exploring Multimodal Composition and Digital Writing, 2014)
What affordances do multimodal and digital information provide to the student and teacher with regard to responding to and writing poetry? This question juxtaposes one of the oldest literary genres in human history (i.e., poetry), with some of the newest technologies available. To enrich the content and effect as students experience poetry, technology may seem like an unwelcome stranger. Research has found, however, that “multimedia texts and multimodal composing may actually shift classroom culture toward a more learner-centered paradigm” (Chandler-Olcott & Mahar, 2003, pp. 381-382). This chapter explores the integration of technology with both response to poetry and authorship of poetic works as a means to enrich English classroom experiences. In the authors’ view, important work in this arena must not use technological tools for the sake of using technology in the classroom, but, rather, for the sake of enriching literary experiences. Ultimately, by connecting response, authorship, and multimodal technologies, the teaching of poetry may be enhanced by the teaching of 21st century literacy skills. Toward these ends, the authors share opportunities for intertwining multimodal text with the teaching of poetry to enrich literacy and literary experience in middle and high school classrooms.
Citation Key Alias: lens.org/010-469-758-942-570
Keywords: dept.cur